2005
DOI: 10.1073/pnas.0506892102
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the blood-brain barrier with high-dose enzyme replacement therapy in murine mucopolysaccharidosis VII

Abstract: Enzyme replacement therapy (ERT) effectively reverses storage in several lysosomal storage diseases. However, improvement in brain is limited by the blood-brain barrier except in the newborn period. In this study, we asked whether this barrier could be overcome by higher doses of enzyme than are used in conventional trials. We measured the distribution of recombinant human ␤-glucuronidase (hGUS) and reduction in storage by weekly doses of 0.3-40 mg͞kg administered i.v. over 1-13 weeks to mucopolysaccharidosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 35 publications
7
121
0
2
Order By: Relevance
“…This is in agreement with our previous studies16 showing that high enzyme doses are necessary to get sufficient amounts of enzyme into the CNS leading to a substantial reduction of brain storage when applied short term, suggesting a dose‐dependent uptake of the recombinant enzyme into the brain. Our studies are in agreement with other preclinical ERT studies in LSD animal models showing mostly beneficial effects of high‐dose injections of recombinant enzymes on primary lysosomal storage reduction and improvement of secondary pathological alterations such as neuroinflammation and behavioral deficits 29, 30, 31, 32, 33. Of note, in our preclinical study, the beneficial effect of ERT was most prominent for the 500 U/kg dosage but still significant at 125 U/kg for most of the parameters analyzed, suggesting that chronic treatment can at least to some extent compensate for lower enzyme activity.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with our previous studies16 showing that high enzyme doses are necessary to get sufficient amounts of enzyme into the CNS leading to a substantial reduction of brain storage when applied short term, suggesting a dose‐dependent uptake of the recombinant enzyme into the brain. Our studies are in agreement with other preclinical ERT studies in LSD animal models showing mostly beneficial effects of high‐dose injections of recombinant enzymes on primary lysosomal storage reduction and improvement of secondary pathological alterations such as neuroinflammation and behavioral deficits 29, 30, 31, 32, 33. Of note, in our preclinical study, the beneficial effect of ERT was most prominent for the 500 U/kg dosage but still significant at 125 U/kg for most of the parameters analyzed, suggesting that chronic treatment can at least to some extent compensate for lower enzyme activity.…”
Section: Discussionsupporting
confidence: 91%
“…Novel potential therapy for mucopolysaccharidoses E Piotrowska et al demonstrated recently that using very high doses of recombinant human b-glucuronidase, it is possible to deliver small amounts of the enzyme to brains of MPS VII mice; 28 however, it is not clear whether this partial overcoming of the blood -brain barrier might be sufficient to cause significant therapeutic effects in mice. Even if so, one might easily imagine various problems (both medical and economical) with provision of very high amounts of the enzyme to human patients suffering from MPS VII and other MPS types.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant phosphorylated hGUS (P-GUS) was produced in CHO cells, and enzyme secreted into conditioned medium was collected and purified as described (18). This enzyme contains showed no enzyme activity in kidney.…”
Section: Methodsmentioning
confidence: 99%
“…Seven days after the last infusion, mice were killed, tissues for GUS assay were frozen in liquid nitrogen, and the samples were processed for histochemical analysis for GUS activity and histological analysis of lysosomal storage (6,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation